Report - Health and Family Planning Services, Indian Systems of Medicine and Homoeopathy, Drugs Control Departments
Vols. for 1973/74-<1974/75> include reports of Dept. of Indian Systems of Medicine and Homoeopathy (called 1973/74 Dept. of Indian Medicine) and Drugs Control Dept.